Empowering Local Communities Through Circular Economy: Transforming Cement Paper Waste into Eco-Friendly Packaging and Handicrafts - Simondinata, Gunawan; Widjaja, Rita; Ciawi, Harry (Society : Jurnal Pengabdian Masyarakat, 2025)
The community surrounding the Indocement factory in Cirebon, particularly women in the assisted villages, faces a lack of skills and limited economic opportunities. Additionally, the factory produces residual paper waste from cement packaging, which is often underutilized. To address these issues, two community engagement initiatives were implemented: (1) crafting eco-friendly "Kotak Mangan" (Mangan boxes) from recycled cement paper waste as sustainable packaging for natural-dye batik products, and (2) training local women to repurpose cement paper waste into marketable handicrafts such as tissue boxes, flower bouquets, and gift boxes. These activities are aligned with the principles of circular economy and supported Indocement's CSR under the Butterfly Diagram framework. The outcomes demonstrated increased environmental awareness, empowerment of women through skill development, and the creation of value-added products from industrial waste, contributing to both economic and ecological sustainability.